Can elderly patients regain their preoperative functional level after distal radius fracture type A? Results from a fracture register study using PROM - Von Matthey, F.; Rammensee, J.; Müller, M.; Biberthaler, P.; Abel, H. (Frontiers in Surgery, 2023)
Introduction Although distal radius fractures (DRF) are the most common fractures of the human body there are still ongoing debates concerning the treatment for type A fractures, especially in the elderly patient. In spite of good clinical outcomes, it remains unclear whether especially elderly patients could regain the preoperative functional level of the wrist. Therefore, we have quantified wrist function within a retrospective study design using PROM and we have analyzed the influence of age between control and patient collective and young versus old, respectively. Patients and Methods: The retrospective study included all patients with a surgically treated DRF type A and a control group of healthy patients, age and gender matched. The function of the wrist was examined with a self-assessment questionnaire the Munich Wrist Questionnaire (MWQ) according to the patient related outcome measurements (PROM). Results: We could enroll 110 patients and controls, the average follow-up was 66 months. Subgroup matching induced similar age group distribution: in both groups, 7 individuals < 30 years, 67 between 31 and 64 years, 29 individuals between 65 and 79 years and 7 individuals > 80 years, were enrolled respectively. In the fracture group women were significantly older than men (59±15 vs. 47±17 (M±SD). There was no significant difference between control and patient group (96±6 vs. 95±7). Function was significantly different between controls and patients < 30 years (100±1 vs. 98±2). In control group there was a functional difference of age group <30 compared to 65-79 and >80 and of age group 30-64 compared to 65-79 and >80. In the control group the function was significantly decreasing with advanced aging whereas in the patient group this influence was absent. Correlation analysis showed worse function with increasing age in the control group and therefore a negative correlation. This result was absent in the fracture group. Discussion: Age has a relevant influence on wrist function. Although the wrist function decreases significantly with ageing, in the patient group this influence was absent and the functional results after surgery are really good. Even elderly patients can regain their pre-operative level.